Mitigating saliva aerosol contamination in a dental school clinic - Maobin Yang; Asad Chaghtai; Marc Melendez; Hana Hasson; Eugene Whitaker; Mustafa Badi; Leona Sperrazza; Jeffrey Godel; Cemil Yesilsoy; Marisol Tellez; Santiago Orrego; Carolina Montoya; et al. (BMC, 2021)
Abstract Background Transmission of COVID-19 via salivary aerosol particles generated when using handpieces or ultrasonic scalers is a major concern during the COVID-19 pandemic. The aim of this study was to assess the spread of dental aerosols on patients and dental providers during aerosol-generating dental procedures. Methods This pilot study was conducted with one volunteer. A dental unit used at the dental school for general dental care was the site of the experiment. Before the study, three measurement meters (DustTrak 8534, PTrak 8525 and AeroTrak 9306) were used to measure the ambient distribution of particles in the ambient air surrounding the dental chair. The volunteer wore a bouffant, goggles, and shoe covers and was seated in the dental chair in supine position, and covered with a surgical drape. The dentist and dental assistant donned bouffant, goggles, face shields, N95 masks, surgical gowns and shoe covers. The simulation was conducted by using a high-speed handpiece with a diamond bur operating in the oral cavity for 6 min without touching the teeth. A new set of measurement was obtained while using an ultrasonic scaler to clean all teeth of the volunteer. For both aerosol generating procedures, the aerosol particles were measured with the use of saliva ejector (SE) and high-speed suction (HSS) followed a separate set of measurement with the additional use of an extra oral high-volume suction (HVS) unit that was placed close to the mouth to capture the aerosol in addition to SE and HSS. The distribution of the air particles, including the size and concentration of aerosols, was measured around the patient, dentist, dental assistant, 3 feet above the patient, and the floor. Results Four locations were identified with elevated aerosol levels compared to the baseline, including the chest of the dentist, the chest of patient, the chest of assistant and 3 feet above the patient. The use of additional extra oral high volume suction reduced aerosol to or below the baseline level. Conclusions The increase of the level of aerosol with size less than 10 µm was minimal during dental procedures when using SE and HSS. Use of HVS further reduced aerosol levels below the ambient levels.